Organ donation video messaging: differential appeal, emotional valence, and behavioral intention. (11th September 2014) - Rodrigue, J. R.; Fleishman, A.; Vishnevsky, T.; Fitzpatrick, S.; Boger, M.
Abstract Video narratives increasingly are used to draw the public's attention to the need for more registered organ donors. We assessed the differential impact of donation messaging videos on appeal, emotional valence, and organ donation intentions in 781 non‐registered adults. Participants watched six videos (four personal narratives, one informational video without personal narrative, and one unrelated to donation) with or without sound (subtitled), randomly sequenced to minimize order effects. We assessed appeal, emotional valence, readiness to register as organ donors, and donation information‐seeking behavior. Compared to other video types, one featuring a pediatric transplant recipient (with or without sound) showed more favorable appeal (p < 0.001), generated more positive emotional valence (p < 0.01), and had the most favorable impact on organ donor willingness (p < 0.001). Ninety‐five (12%) participants clicked through to a donation website after viewing all six videos. Minority race (OR = 1.94, 95% CI = 1.20, 3.13, p = 0.006), positive change in organ donor readiness (OR = 0.26, 95% CI = 0.14, 0.48, p < 0.001), and total positive emotion (OR = 1.05, 95% CI = 1.03, 1.07, p < 0.001) were significant multivariable predictors of clicking through to the donation website. Brief, one‐min videos can have a very dramatic and positive impact on willingness to consider donation and behavioral intentions to register as an organ donor.